The Impact of Chemotherapy on the Chronic Inflammation Caused by Escherichia coli Infection and Insulin Resistance in Type 2 Diabetes-Associated Prostate Cancer Patients - Faisal, Anwer Jaber; Saeed, Baraa Ahmed; Sabri Shawkat, Rabiah Muayad; Mohammed, Abbas A; kareem Kadhim, Noor; Shaker Mahmood, Bassam (Asian Pacific Journal of Cancer Biology, 2025)
Background: The most common malignancy in men is prostate cancer. Chronic inflammation and bacterial infections exacerbate insulin resistance in type 2 diabetes (T2D) patients, potentially worsened by chemotherapy in those with prostate cancer. This study investigates the effects of Docetaxel chemotherapy on systemic inflammation, Insulin Resistance, and bacterial resistance in T2D patients with prostate cancer. Methods: Eighty participants (aged 50–75 years) were enrolled in a cross-sectional study and divided into four groups: Group 1 (T2D without cancer, n=40), Group 2 (T2D with prostate cancer, pre-chemotherapy, n=40), Group 3 (Group 2 subset post-two Docetaxel cycles), and Group 4 (Group 2 subset post-five Docetaxel cycles). Serum levels of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), procalcitonin (PCT), fasting glucose, fasting insulin, and prostate-specific antigen (PSA) were measured via immunoassays. Insulin resistance was assessed using the Homeostatic Model Assessment (HOMA-IR). Urine samples were analyzed for Escherichia coli isolation and antibiotic resistance via the Kirby-Bauer method. Statistical significance was determined using t-tests (P≤0.05). Results: Group 4 exhibited notably elevated inflammatory markers (PCT, IL-6, TNF-α), fasting glucose, fasting insulin, PSA, and the value of HOMA-IR compared to Groups 1–3 (P≤0.01). E. coli isolation rates increased from 67.5% (Group 2) to 80% (Group 4, P=0.20), with antibiotic resistance rising, notably for Amikacin (17.5% to 35%, P=0.08) and Nitrofurantoin (25% to 30%, P=0.61), though these differences were not statistically significant. Multidrug-resistant (MDR) and extensively drug-resistant (XDR) isolates also increased slightly post-chemotherapy. Conclusion: Docetaxel chemotherapy in T2D prostate cancer patients is associated with heightened systemic inflammation, insulin resistance, and bacterial resistance, underscoring the need for integrated therapeutic strategies to mitigate these effects.